KOMPARASI NAHWU DALAM BAHASA ARAB DAN SINTAKSIS DALAM BAHASA INDONESIA PADA MAHASISWA PENDIDIKAN BAHASA ARAB IAIN PALU - M. Asy'ari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2016)
Contrastive study has been popular in some Islamic universities which are studying the Arabic language, especially in the Department of Arabic Language Faculty of IAIN Palu which need contrastive research results for the lecturers of Arabic in the field. Therefore, the difficulty and the ease of learning the Arabic language will be able to feel the benefits. Contrastive study is expected to produce a number of similarities and differences Indonesian first language (BI) students with a second language (B2) being studied on campus. Based on the results of the discussion and data analysis, interview with several students, namely: M.Arinal Haq, Hilal and others who have difficulty in answering syntactic/nahwu test as well as interview with experts/senior lecturers of nahwu namely: Dr. H. Ahmad Sehri and H. Ubadah, researcher can explain the difficulties/problems of nahwu on the ground that the students who find it difficult to be detected from the experience and analysis of their answers, namely: lack of understanding of the fa'il concept when it`s associated with dhamir mustatir, mostly students still do not understand the concept of mudhaf idhafah, na'at, tawkid and others